(untitled) (Journal of Asian Development Studies, 2026)
The effects of exchange rate shock, monetary policy shock and demand shock on economic growth is investigated in Turkish Economy for the period from 2005:M1 to 2015M10. Monthly data is used in the analysis. Results of the empirical tests prove that the growth in Turkey is associated with the exchange rate shocks, monetary policy shocks and demand shocks respectively in a decreasing scale. The policies such as volatile exchange rate policy and inflation targeting are also considerable in the period.